Page 2 of 8 FirstFirst 123456 ... LastLast
Results 16 to 30 of 106

Math Help - Prove some identities!

  1. #16
    Super Member
    Joined
    Jan 2009
    Posts
    715
    To stop this thread from being moved to the second page of the subforum . I would like to
    give my solutions to these three integrals I posted previously . Hope more and more wonderful identities will be created here !

    Problem :


    Let  K = \frac{\ln^2(1+\sqrt{2})}{2}
    Show that :
     \displaystyle \int_1^{\infty} \frac{\ln(x+\sqrt{x^2 - 1} )}{x(x^2 +1 )}~dx = K
     \displaystyle \int_1^{\infty}\frac{\tan^{-1}(x)}{x\sqrt{x^2 - 1 } }~dx = \frac{\pi^2}{8} + K
     \displaystyle \int_0^1 \frac{\tan^{-1}(x)}{\sqrt{1-x^2} }~dx = \frac{\pi^2}{8} - K

    Solution to the fisrt integral :
    Spoiler:


     I = \int_1^{\infty} \frac{\ln(x + \sqrt{x^2 - 1} )}{x(x^2+1)}~dx
    Integration by parts ,

     I = \left[ \ln{\left( \frac{x}{\sqrt{x^2 + 1 }} \right)} \ln(x + \sqrt{x^2 - 1 } ) \right]_1^{\infty} - \int_1^{\infty} \ln{\left( \frac{x}{\sqrt{x^2 + 1 }} \right)} ~ \frac{dx}{\sqrt{x^2 - 1 } }

     = - \int_1^{\infty} \ln{\left( \frac{x}{\sqrt{x^2 + 1 }} \right)} ~ \frac{dx}{\sqrt{x^2 - 1 } }


    Use  x \mapsto 1/x we have

     I = \frac{1}{2} \int_0^1 \frac{\ln(x^2+1)}{x \sqrt{1-x^2}}~dx

     = \int_0^1 \left[ \int_0^1 \frac{xt dx}{(x^2t^2+1)\sqrt{1-x^2} }\right] ~dt

    Sub.  \sqrt{1-x^2} = y ,  - \frac{xdx}{\sqrt{1-x^2} } = dy

     I = \int_0^1 \int_0^1 \frac{tdy}{t^2+1 -t^2y^2} ~dt

     = \int_0^1 \frac{\ln(\sqrt{1+t^2} + t )}{\sqrt{t^2+1} }~dt <br />

     = \left[ \frac{\ln^2(\sqrt{1+t^2} + t ) }{2} \right]_0^1 = K


    Solution to the second integral :
    Spoiler:
    Sub.  x = 1/t and we will find that it is similar to the third integral . See the solution of the third integral


    Solution to the third integral :
    Spoiler:

    Let
     I(t) = \int_0^1 \frac{\tan^{-1}(tx)}{\sqrt{1-x^2}}~dx
    Then

     I'(t) = \int_0^1 \frac{x~dx}{(1+t^2 x^2)\sqrt{1-x^2} }

    Sub.  \sqrt{1-x^2}=y ,  - \frac{x~dx}{\sqrt{1-x^2}}= dy

     I'(t) = \int_0^1 \frac{dy}{1+t^2 - t^2y^2 }
     = \frac{1}{2t\sqrt{1+t^2}} \ln{\left[ \frac{\sqrt{1+t^2}+ t}{\sqrt{1+t^2} - t } \right]}
     = \frac{1}{t\sqrt{1+t^2}}\ln( \sqrt{1+t^2} + t )

    We have

     I(1) - I(0) = \int_0^1 \frac{dt}{t\sqrt{1+t^2}}\ln( \sqrt{1+t^2} + t )

    Integration by parts ,

     I(1) - I(0) = \left[- \ln(\sqrt{1+t^2} + t ) \ln( \sqrt{1+1/t^2 } +1/t ) \right]_0^1 +\int_0^1 \ln( \sqrt{1+1/t^2 } +1/t ) \frac{dt}{\sqrt{1+t^2}}

     = -2K + \int_0^1 \ln( \sqrt{1+1/t^2 } +1/t ) \frac{dt}{\sqrt{1+t^2}}

    Sub.  t = 1/x

     I(1) - I(0) = -2K + \int_1^{\infty} \ln( \sqrt{1+x^2} + x ) \frac{dx}{x\sqrt{1+x^2} } = -2K + I(\infty) - I(1)

    But

     I(1) = \int_0^1 \frac{\tan^{-1}(x)}{\sqrt{1-x^2}}~dx

     I(0) = 0

     I(\infty) = \frac{\pi}{2} \int_0^1 \frac{dx}{\sqrt{1-x^2 } } = \frac{\pi^2}{4} so we have

     2 I(1) = -2K + \frac{\pi^2}{4}

     \int_0^1 \frac{\tan^{-1}(x)}{\sqrt{1-x^2}}~dx = \frac{\pi^2}{8} - K
    Follow Math Help Forum on Facebook and Google+

  2. #17
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    This may be too easy, but I find this one surprising.

    Compute \displaystyle \lim_{\lambda\to\infty}\int_0^1|\sin(\lambda x)|\text { }dx
    Follow Math Help Forum on Facebook and Google+

  3. #18
    Super Member
    Joined
    Jan 2009
    Posts
    715
    I don't know whether my solution is correct or not , please take a look .


    Let  k = [\frac{t}{\pi}] and  a = \frac{\pi}{t}

     I(t) =\int_0^1 |\sin(tx)|~dx

     = \left(  \int_0^a + \int_a^{2a} + ... + \int_{(k-1)a}^{ka} + \int_{ka}^1 \right) |\sin(tx)|~dx

     = k(\frac{2}{t} ) + \int_{ka}^1 |\sin(tx)|~dx

    so  \frac{2k}{t} \leq I(t) < \frac{2k}{t } + \frac{2}{t}

     \displaystyle{ \lim_{t\to\infty} \frac{2k}{t} \leq \lim_{t\to\infty} I(t) <  \lim_{t\to\infty} [\frac{2k}{t } + \frac{2}{t} ]

    But   \frac{1}{\pi} - \frac{1}{t} <  \frac{k}{t} \leq \frac{1}{\pi} so

     \displaystyle{ \lim_{t\to\infty} \frac{2k}{t} = \frac{2}{\pi} } and

     \displaystyle{ \lim_{t\to\infty} I(t)   = \frac{2}{\pi}}
    Follow Math Help Forum on Facebook and Google+

  4. #19
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    Quote Originally Posted by simplependulum View Post
    I don't know whether my solution is correct or not , please take a look .


    Let  k = [\frac{t}{\pi}] and  a = \frac{\pi}{t}

     I(t) =\int_0^1 |\sin(tx)|~dx

     = \left(  \int_0^a + \int_a^{2a} + ... + \int_{(k-1)a}^{ka} + \int_{ka}^1 \right) |\sin(tx)|~dx

     = k(\frac{2}{t} ) + \int_{ka}^1 |\sin(tx)|~dx

    so  \frac{2k}{t} \leq I(t) < \frac{2k}{t } + \frac{2}{t}

     \displaystyle{ \lim_{t\to\infty} \frac{2k}{t} \leq \lim_{t\to\infty} I(t) <  \lim_{t\to\infty} [\frac{2k}{t } + \frac{2}{t} ]

    But   \frac{1}{\pi} - \frac{1}{t} <  \frac{k}{t} \leq \frac{1}{\pi} so

     \displaystyle{ \lim_{t\to\infty} \frac{2k}{t} = \frac{2}{\pi} } and

     \displaystyle{ \lim_{t\to\infty} I(t)   = \frac{2}{\pi}}
    It looks the similar to mine. Could you explain it a bit more. In particular what the notation, especially the second step (with the sum of integrals in the parentheses means). Anyways, here's mine


    Spoiler:

    If L is our limit then, assuming that \lambda>\pi,


    \displaystyle \begin{aligned}L=\lim_{\lambda\to\infty}\frac{1}{\  lambda}\int_0^{\lambda}|\sin(x)|\text{ }dx &=\lim_{\lambda\to\infty}\left\{\frac{1}{\lambda}\  sum_{k=1}^{\left\lfloor\frac{\lambda}{\pi}\right\r  floor}\int_{\pi(k-1)}^{\pi k}|\sin(x)|\text{ }dx+\frac{1}{\lambda}\int_{\pi\left\lfloor\frac{\l  ambda}{\pi}\right\rfloor}^{\lambda}|\sin(x)|\text{ }dx\right\}\\ &= \lim_{\lambda\to\infty}\left\{\frac{2\left\lfloor\  frac{\lambda}{\pi}\right\rfloor}{\lambda}+\frac{1}  {\lambda}\int_{\pi\left\lfloor\frac{\lambda}{\pi}\  right\rfloor}^{\lambda}|\sin(x)|\text{ }dx\right\}\\ &=\lim_{\lambda\to\infty}\left\{ \frac{2}{\pi}+\frac{\pi \xi_{\lambda}}{\lambda}\right\}\end{aligned}

    Where 0\leqslant \xi_{\lambda}\leqslant 2 from where it follows that \displaystyle L=\frac{2}{\pi}.

    Follow Math Help Forum on Facebook and Google+

  5. #20
    Super Member
    Joined
    Jan 2009
    Posts
    715
    Quote Originally Posted by Drexel28 View Post
    It looks the similar to mine. Could you explain it a bit more. In particular what the notation, especially the second step (with the sum of integrals in the parentheses means). Anyways, here's mine
    Sure , my idea is similar to yours :
    As the period of the integrand is  a = \frac{\pi}{t} ( t here is the same as  \lambda ) I first partitioned the interval  (0,1) into  (0,a) , (a,2a) ,..., ((k-1)a,ka) , (ka,1) . For  x \in (0,a)  we have   0 < tx < ta = \pi  which yields  \sin(tx) >0  so we find that the values of the first k summands are the same (  = \int_0^a \sin(tx)~dx = \frac{2}{t} ) . For the last summand ,  \int_{ka}^1 |\sin(tx)|~dx , we know it is less than  \int_0^a \sin(tx)~dx = \frac{2}{t} . Therefore ,  \frac{2k}{t} \leq I(t) < \frac{2k}{t} + \frac{2}{t}  . Then i used squeeze principle to evaluate the limit .
    Follow Math Help Forum on Facebook and Google+

  6. #21
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    Quote Originally Posted by simplependulum View Post
    Sure ,my idea is :

    First partition the interval  (0,1) into  (0,a) , (a,2a) ,..., ((k-1)a,ka) , (ka,1) with  a = \frac{\pi}{t} ( t here is the same as  \lambda ) . We find that the value of the first k summands are the same (  = \int_0^a \sin(tx)~dx = \frac{2}{t} ) . For the last summand ,  \int_{ka}^1 |\sin(tx)|~dx , we know it is less than  \int_0^a \sin(tx)~dx = \frac{2}{t} . Therefore ,  \frac{2k}{t} \leq I(t) < \frac{2k}{t} + \frac{2}{t}  . Then i used squeeze principle to evaluate the limit .
    Ah, I understand better now. Thanks.
    Follow Math Help Forum on Facebook and Google+

  7. #22
    Super Member
    Joined
    Jan 2009
    Posts
    715

    Three Integrals

    What about these ? The first one is very easy but on the way we generalize this integral , it becomes harder and harder ...


    1.  I_n =  \int_0^{\pi} \frac{\sin(nx)}{\sin(x)}~dx

    2.  I_n =  \int_0^{\pi} \frac{\sin^2(nx)}{\sin^2(x)}~dx

    3.  I_n =  \int_0^{\pi} \frac{\sin^3(nx)}{\sin^3(x)}~dx
    Follow Math Help Forum on Facebook and Google+

  8. #23
    Super Member PaulRS's Avatar
    Joined
    Oct 2007
    Posts
    571
    Quote Originally Posted by simplependulum View Post
    What about these ? The first one is very easy but on the way we generalize this integral , it becomes harder and harder ...


    1.  I_n =  \int_0^{\pi} \frac{\sin(nx)}{\sin(x)}~dx

    2.  I_n =  \int_0^{\pi} \frac{\sin^2(nx)}{\sin^2(x)}~dx

    3.  I_n =  \int_0^{\pi} \frac{\sin^3(nx)}{\sin^3(x)}~dx

    See here
    Last edited by PaulRS; December 21st 2010 at 03:12 AM.
    Follow Math Help Forum on Facebook and Google+

  9. #24
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    This also might be too easy, but how about \displaystyle \lim_{x\to 0}\frac{x^n}{\Gamma\left(x^n+1)-1}. Or, how about \displaystyle \sum_{n=1}^{\infty}\frac{\alpha n+\beta}{n(n+1)\cdots(n+\ell)},\text{ }\ell\in\mathbb{N},\text{ }\ell\geqslant 3
    Follow Math Help Forum on Facebook and Google+

  10. #25
    Member
    Joined
    Nov 2009
    Posts
    106
    Quote Originally Posted by Drexel28 View Post
    This also might be too easy, but how about \displaystyle \lim_{x\to 0}\frac{x^n}{\Gamma\left(x^n+1)-1}. Or, how about \displaystyle \sum_{n=1}^{\infty}\frac{\alpha n+\beta}{n(n+1)\cdots(n+\ell)},\text{ }\ell\in\mathbb{N},\text{ }\ell\geqslant 3
    For the limit, use L'hospital's rule and see that this is equal \frac{1}{\Gamma'(1)} = -\frac{1}{\gamma}

    For the sum, we first evaluate:

    \displaystyle{S(\ell) = \sum_{n=1}^\infty \frac{1}{n(n+1)\cdots (n+\ell)}

    Consider the following polynomial in n:

    <br />
\displaystyle{P(n) = <br />
\sum_{k=1}^\ell (-1)^k\binom{\ell}{k}\prod_{\substack{r=0\\r\ne k}}^\ell} (n+r)<br />
}<br />

    Then we have:

    \displaystyle{\deg P \le \ell\:\:\:\:;\:\:\:\:\:P(0)=P(-1)=P(-2)=\dots =P(-\ell) = \ell !}

    and therefore

    \displaystyle{\ell ! \equiv P(n) = \sum_{k=1}^\ell (-1)^k\binom{\ell}{k}\prod_{\substack{r=0\\r\ne k}}^\ell} (n+r)}

    Divide both sides by

    \displaystyle{\ell ! \prod_{k=0}^\ell (n+k)}

    to get the following identity:

    <br />
\displaystyle{<br />
\frac{1}{\displaystyle\prod_{k=0}^\ell (n+k)} = \frac{1}{\ell !}\sum_{k=0}^\ell \frac{(-1)^k \binom{\ell}{k}}{n+k}<br />
}<br />

    from which we obtain:

    \displaystyle{<br />
S(\ell) = \sum_{n=1}^\infty \frac{1}{n(n+1)\cdots (n+\ell)} = \frac{1}{\ell !}\sum_{k=0}^\ell\left[ (-1)^k \binom{\ell}{k}\sum_{n=1}^\infty \frac{1}{n+k}\right]<br />
}

    \displaystyle{<br />
= \lim_{m\rightarrow\infty} \frac{1}{\ell !}\sum_{k=0}^\ell\left[ (-1)^k \binom{\ell}{k}(H_{m+k}-H_{k})\right]<br />
}

    where H_n is the n'th harmonic number (setting H_0 = 0).

    Substituting H_{m+k} = (H_{m+k}-H_{m}) + H_{m} and using

    \displaystyle{<br />
\lim_{m\rightarrow\infty} (H_{m+k}-H_{m}) = 0<br />
}

    together with

    \displaystyle{<br />
\sum_{k=0}^\ell (-1)^k\binom{\ell}{k} = 0<br />
}

    we get

    \displaystyle{<br />
S(\ell) = -\frac{1}{\ell !}\sum_{k=0}^\ell (-1)^k\binom{\ell}{k}H_{k} = \frac{1}{\ell !}\sum_{k=0}^\ell \left[(-1)^k\binom{\ell}{k}\int_0^1 \frac{t^k-1}{1-t}dt\right]<br />
}


    \displaystyle{<br />
=\frac{1}{\ell !}\int_0^1 \frac{\displaystyle\sum_{k=0}^\ell (-t)^k\binom{\ell}{k}}{1-t}dt = \frac{1}{\ell !}\int_0^1 \frac{(1-t)^\ell}{1-t}dt<br />
}


    \displaystyle{<br />
= \frac{1}{\ell !}\int_0^1 t^{\ell-1}dt = \frac{1}{\ell \cdot \ell !}<br />
}


    Therefore in the proposed problem:


    \displaystyle{\sum_{n=1}^{\infty}\frac{\alpha n+\beta}{n(n+1)\cdots(n+\ell)}}


    \displaystyle{ = \alpha\sum_{n=1}^{\infty}\frac{1}{(n+1)\cdots(n+\e  ll)}}+\beta\sum_{n=1}^{\infty}\frac{1}{n(n+1)\cdot  s(n+\ell)}}

    \displaystyle{<br />
=\alpha \left(S(\ell-1)-\frac{1}{\ell!}\right)+\beta S(\ell) = \frac{1}{\ell !}\left(\frac{\alpha}{\ell-1}+\frac{\beta}{\ell}\right)<br />
}<br />
    Follow Math Help Forum on Facebook and Google+

  11. #26
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    Quote Originally Posted by Unbeatable0 View Post
    For the limit, use L'hospital's rule and see that this is equal \frac{1}{\Gamma'(1)} = -\frac{1}{\gamma}
    We don't use L'hopital's around these parts! That said, it was so easy that might as well accept that. >

    Also, I like your method! It was totally different than what I did! Which was:

    Spoiler:


    Note that our sum can be written \displaystyle K(\ell)+J(\ell) where \displaystyle K(\ell)=\alpha\sum_{n=1}^{\infty}\frac{1}{(n+1)\cd  ots(n+\ell)} and \displaystyle J(\ell)=\beta\sum_{n=1}^{\infty}\frac{1}{n(n+1)\cd  ots(n+\ell)}. Note firstly then that

    \displaystyle \begin{aligned}K(\ell) &= \frac{\alpha}{(\ell-1)!}\sum_{n=1}^{\infty}\frac{n!(\ell-1)!}{(n+\ell)!}\\ &= \frac{\alpha}{(\ell-1)!}\sum_{n=1}^{\infty}\frac{\Gamma(n+1)\Gamma(\el  l)}{\Gamma(n+\ell+1)}\\ &= \frac{\alpha}{(\ell-1)!}\sum_{n=1}^{\infty}B(n+1,\ell)\\ &= \frac{\alpha}{(\ell-1)!}\sum_{n=1}^{\infty}\int_0^1 t^{n}(1-t)^{\ell-1}\text{ }dt\\ &= \frac{\alpha}{(\ell-1)!}\int_0^1 (1-t)^{\ell-1}\sum_{n=1}^{\infty}t^n\text{ }dt\\ &=\frac{\alpha}{(\ell-1)!}\int_0^1 (1-t)^{\ell-2}-(1-t)^{\ell-1}\text{ }dt\\ &= \frac{\alpha}{(\ell-1)!} \frac{1}{\ell(\ell-1)}\\ &= \frac{\alpha}{\ell! (\ell-1)}\end{aligned}

    and similarly


    \displaystyle \begin{aligned}J(\ell) &= \frac{\beta}{\ell!}\sum_{n=1}^{\infty}\frac{(n-1)!\ell!}{(n+\ell)!}\\ &= \frac{\beta}{\ell!}\sum_{n=1}^{\infty}\frac{\Gamma  (n)\Gamma(\ell+1)}{\Gamma(n+\ell+1)}\\ &= \frac{\beta}{\ell!}\sum_{n=1}^{\infty}B(n,\ell+1)\  \ &= \frac{\beta}{\ell!}\sum_{n=1}^{\infty}\int_0^1 t^{n-1}(1-t)^\ell\text{ }dt\\ &= \frac{\beta}{\ell!}\int_0^1 (1-t)^{\ell}\sum_{n=1}^{\infty}t^{n-1}\text{ }dt\\ &= \frac{\beta}{\ell!}\int_0^1 (1+t)^{\ell-1}\text{ }dt\\ &= \frac{\beta}{\ell!\ell}\end{aligned}

    Thus,

    \displaystyle \sum_{n=1}^{\infty}\frac{\alpha n+\beta}{n(n+1)\cdots(n+\ell)}=K(\ell)+J(\ell)=\fr  ac{\alpha}{\ell!(\ell-1)}+\frac{\beta}{\ell!\ell}=\frac{1}{\ell!}\left(\  frac{\alpha}{\ell-1}+\frac{\beta}{\ell}\right)

    Same as yours!




    I propose three more problems in increasing difficulty:

    This first one is super-easy but try to do it in a non-obvious way. Anyways, it's an interesting result!

    Problem 1: Prove that for n\in\mathbb{N}

    \displaystyle \sum_{k=1}^{n}{n\choose k}\frac{(-1)^{k+1}}{k}=\sum_{k=0}^{n-1}\frac{1}{k+1}

    Problem 2: For k,n\in\mathbb{N} such that n-k-1\geqslant 1 compute

    \displaystyle \sum_{t=0}^{n-k-1}\frac{(-1)^t}{k+t+1}{{n-k-1}\choose t}

    Have fun with this one (you won't, unless you 'see it')

    Problem 3: Compute

    \displaystyle \lim_{n\to\infty}(n+1)\int_0^1 x^n \Gamma^3(x+1)\zeta^3(x+3)\text{ }dx
    Follow Math Help Forum on Facebook and Google+

  12. #27
    Member
    Joined
    Nov 2009
    Posts
    106
    I like your method very much! Although I liked my solution for being elementary, yours is far more elegant.

    Quote Originally Posted by Drexel28 View Post
    This first one is super-easy but try to do it in a non-obvious way. Anyways, it's an interesting result!
    What is an obvious way for this? The following?

    \displaystyle{<br />
\sum_{k=0}^{n-1}\frac{1}{k+1} = \sum_{k=0}^{n-1}\int_0^1 x^k dx = \int_0^1\frac{x^n-1}{x-1}dx<br />
}

    and then substituting x\mapsto 1-x and using Newton's binom, gives the result.


    For problem 2, it's the same method:

    \displaystyle{<br />
\sum_{t=0}^{n-k-1}\frac{(-1)^t}{k+t+1}\binom{n-k-1}{t} = (-1)^k\sum_{t=0}^{n-k-1}\int_0^1 (-x)^{k+t}\binom{n-k-1}{t}dx<br />
}


    \displaystyle{<br />
= (-1)^k\int_0^1 (-x)^k \sum_{t=0}^{n-k-1}(-x)^t\binom{n-k-1}{t}dx<br />
}


    \displaystyle{<br />
= \int_0^1 x^k(1-x)^{n-k-1}dx<br />
}

    \displaystyle{<br />
= B(k+1,n-k) = \frac{k!(n-k-1)!}{n!}<br />
}

    Was this your method? If not, I'm interested to see how you solved it.

    I'd be glad to post some problems, but none have come to my mind thus far, and in the last days I haven't encoutered with any challenge problems which would fit this thread. I will, however, keep looking for nice problems to post in here.
    Last edited by Unbeatable0; December 23rd 2010 at 05:22 AM.
    Follow Math Help Forum on Facebook and Google+

  13. #28
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    Quote Originally Posted by Unbeatable0 View Post
    I like your method very much! Although I liked my solution for being elementary, yours is far more elegant.
    Thank you!


    Was this your method? If not, I'm interested to see how you solved it.
    I had a mental lapse. There is another problem which is super easy to do using analysis/calculus but has other interesting ways to do it. It's (go ahead and try it) compute

    \displaystyle \sum_{j=1}^{n}j{j\choose n}

    Although I just realized you can do this by a little trickery similar to what you did for your proof of the previous problem using Retkes's identities.

    I'd be glad to post some problems, but none have come to my mind thus far, and in the last days I haven't encoutered with any challenge problems which would fit this thread. I will, however, keep looking for nice problems to post in here.
    Here is quite a beautiful one (in my opinion).

    Problem: Let \Omega\subseteq\mathbb{R}^n be the set of all (x_1,\cdots,x_n) such that x_j\geqslant 0,\text{ }j\in[n] and \displaystyle \sum_{j=1}^{n}x_j=1. Compute


    \displaystyle \int\cdots\int_{\Omega}x^{\alpha_1-1}\cdots x^{\alpha_n-1}\text{ }dx_1\cdots dx_n


    where \text{Re }\alpha_k>0,\text{ }k\in[n].
    Follow Math Help Forum on Facebook and Google+

  14. #29
    Member
    Joined
    Nov 2009
    Posts
    106
    Quote Originally Posted by Drexel28 View Post
    \displaystyle \sum_{j=1}^{n}j{j\choose n}

    Although I just realized you can do this by a little trickery similar to what you did for your proof of the previous problem using Retkes's identities.
    I looked up Retkes's identities, but don't understand how you meant to apply them. Care to clarify?

    Also, you had a little typo there - the binomial should have been upside down.

    Besides the usual proof for this identity, using the derivative of

    <br />
\displaystyle{<br />
\sum_{k=0}^n \binom{n}{k} x^k = (1+x)^n<br />
}<br />

    I've just found a much more elegant (in my opinion) method: let k\mapsto n-k in the summation to get:

    <br />
\displaystyle{<br />
\sum_{k=1}^n k\binom{n}{k} = \sum_{k=0}^n k\binom{n}{k} = \sum_{k=0}^n (n-k)\binom{n}{k} = n\sum_{k=0}^n \binom{n}{k} - \sum_{k=0}^n k\binom{n}{k}<br />
}<br />

    Now using

    <br />
\displaystyle \sum_{k=0}^n \binom{n}{k} = 2^n<br />

    gives the result.




    Edit: an easy problem - prove the following generalization:
    Edit 2: there was a little mistake here. Fixed it now.

    \displaystyle{<br />
\sum_{k=0}^n n^m\binom{n}{k}= 2^nn!\sum_{k=0}^m\frac{\left\{{m\atop k}\right\} }{2^k(n-k)!}<br />
}

    where \left\{{m\atop k}\right\} are the Stirling numbers of the second kind, m\in\mathbb{N}_0.



    I'd try the other problem you proposed, but I haven't yet covered multivariable integrals .
    Last edited by Unbeatable0; December 24th 2010 at 12:57 AM.
    Follow Math Help Forum on Facebook and Google+

  15. #30
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    Quote Originally Posted by Unbeatable0 View Post
    I looked up Retkes's identities, but don't understand how you meant to apply them. Care to clarify?
    Try applying Retkes' third identity (the one with the sum of the reciporcals) and recalling that \Pi_j(1,\cdots,n)=(-1)^{n-j}(j-1)!(n-j)!


    Also, you had a little typo there - the binomial should have been upside down.
    Of course! The first proof is the one I had in mind and the second one is nice indeed! I did it by double counting.



    I'd try the other problem you proposed, but I haven't yet covered multivariable integrals .
    Haha, oh well!
    Follow Math Help Forum on Facebook and Google+

Page 2 of 8 FirstFirst 123456 ... LastLast

Similar Math Help Forum Discussions

  1. Can't prove these identities?
    Posted in the Trigonometry Forum
    Replies: 6
    Last Post: November 20th 2010, 07:07 AM
  2. prove the following identities.
    Posted in the Trigonometry Forum
    Replies: 3
    Last Post: June 22nd 2010, 11:15 PM
  3. Can someone help me prove these two identities?
    Posted in the Trigonometry Forum
    Replies: 5
    Last Post: April 7th 2010, 12:48 PM
  4. prove identities
    Posted in the Trigonometry Forum
    Replies: 1
    Last Post: June 25th 2009, 11:08 PM
  5. Prove identities, can anyone help?
    Posted in the Trigonometry Forum
    Replies: 3
    Last Post: February 14th 2009, 01:04 PM

Search Tags


/mathhelpforum @mathhelpforum